Study Analysis of the Need for the Mobile Learning Model Learning Based on Problem Based Learning in Learning Citizenship Education in Senior High School - Khairil Anwar; Sahat Siagian; R. Mursid (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to analyze the needs of developing PBL-based mobile learning learning models. The study was conducted using a survey method of High Schools in the City of Pematang Siantar. The research subjects were 18 class teachers who taught Pancasila and Citizenship Education learning. The object being studied is the responses of school principals and teachers to the development of PBL-based mobile learning models, the tendency of teachers to apply PBL-based mobile learning models in schools, student reasoning, and student character. Data collected by interview, questionnaire, observation, and test. Data were analyzed descriptively. The analysis shows that (1) school principals have not yet fostered the development of PBL-based mobile learning learning models, so they support development efforts, (2) teachers have not yet developed and used PBL-based mobile learning learning models, so they support and declare readiness to be involved in the development, (3) learning models used by teachers so far there have been no indications leading to PBL-based mobile learning learning models.